Description and ecophysiology of a new species of Syndesmis Silliman, 1881 (Rhabdocoela: Umagillidae) from the sea urchin Evechinus chloroticus (Valenciennes, 1846) Mortensen, 1943 in New Zealand - Monnens, Marlies; Frost, Emily J; Clark, Miriam; Sewell, Mary A; Vanhove, Maarten P M; Artois, Tom (International journal for parasitology. Parasites and wildlife, 2019)
A new rhabdocoel of the genus Syndesmis Silliman, 1881 (Umagillidae) is described from the intestine of the New Zealand sea urchin Evechinus chloroticus (Valenciennes, 1846) Mortensen, 1943a. This new species, Syndesmis kurakaikina n. sp., is morphologically distinct and can easily be recognised by its very long (±1 mm) stylet and its bright-red colour. In addition to providing a formal description, we present some observations on reproduction and life history of this new species. Fecundity is comparable to that of other umagillids and the rate of egg production and development increases with temperature. Hatching in this species is induced by intestinal fluids of its host. Relevant to global warming, we assessed the effect of temperature on survival, fecundity, and development. The tests indicate that Syndesmis kurakaikina n. sp. is tolerant of a wide range of temperatures (11-25 °C) and that its temperature optimum lies between 18.0 and 21.5 °C. Egg viability is, however, significantly compromised at the higher end of this temperature range, with expelled egg capsules often being deformed and showing increasingly lower rates of hatching. Given this, a rise in global temperature might increase the risk of Syndesmis kurakaikina n. sp. infecting new hosts and would possibly facilitate the spread of these endosymbionts.